2018
DOI: 10.14739/2310-1210.2018.3.132124
|View full text |Cite
|
Sign up to set email alerts
|

Etiological and pathogenetic aspects of non-specific bacterial vaginosis

Abstract: The aim of this review was the biological properties analysis of microorganisms known as the main contributors to the non-specific bacterial vaginosis development.The mechanisms of anaerobic vaginal microflora pathogenic action have been found out to be the main cause of non-specific inflammatory processes. Special attention was given to the genera of Mobilunkus spp., Atopobium spp., Prevotella sp. representatives, which were studied as vaginal flora due to the modern diagnostic methods and techniques developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…On the contrary, verification of Trichomonas tenax and Pentatrichomonas hominis in the urinary tract using the real-time PCR method was maximally informative. Therefore, it was suggested that during trichomonad verifications by inoculation on the appropriate nutrient medium often take Trichomonas non vaginalis is often confused with Trichomonas vaginalis, namely Trichomonas tenax or Pentatrichomonas hominis [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, verification of Trichomonas tenax and Pentatrichomonas hominis in the urinary tract using the real-time PCR method was maximally informative. Therefore, it was suggested that during trichomonad verifications by inoculation on the appropriate nutrient medium often take Trichomonas non vaginalis is often confused with Trichomonas vaginalis, namely Trichomonas tenax or Pentatrichomonas hominis [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Основными компонентами индигенной (постоянной) микробиоты влагалища являются лактобациллы, бифидобактерии и пропионовокислые бактерии, суммарная доля которых составляет не менее 95 %. Эволюция влагалищного биотопа обусловила выработку адаптационных механизмов, позволяющих микроорганизмам, входящих в состав нормальной микрофлоры, активно развиваться во влагалищной среде, адгезировать на эпителии, образуя с ним прочные симбиотические связи, и успешно конкурировать с факультативной и транзиторной условно-патогенной и патогенной микробиотой [4,9,10].…”
Section: Introductionunclassified